Critical role of the disintegrin metalloprotease ADAM17 for intestinal inflammation and regeneration in mice - Chalaris, Athena; Adam, Nina; Sina, Christian; Rosenstiel, Philip; Lehmann-Koch, Judith; Schirmacher, Peter; Hartmann, Dieter; Cichy, Joanna; Gavrilova, Olga; Schreiber, Stefan; Jostock, Thomas; Matthews, Vance; et al. (Journal of experimental medicine, 2010)
The protease a disintegrin and metalloprotease (ADAM) 17 cleaves tumor necrosis factor (TNF), L-selectin, and epidermal growth factor receptor (EGF-R) ligands from the plasma membrane. ADAM17 is expressed in most tissues and is up-regulated during inflammation and cancer. ADAM17-deficient mice are not viable. Conditional ADAM17 knockout models demonstrated proinflammatory activities of ADAM17 in septic shock via shedding of TNF. We used a novel gene targeting strategy to generate mice with dramatically reduced ADAM17 levels in all tissues. The resulting mice called ADAM17(ex/ex) were viable, showed compromised shedding of ADAM17 substrates from the cell surface, and developed eye, heart, and skin defects as a consequence of impaired EGF-R signaling caused by failure of shedding of EGF-R ligands. Unexpectedly, although the intestine of unchallenged homozygous ADAM17(ex/ex) mice was normal, ADAM17(ex/ex) mice showed substantially increased susceptibility to inflammation in dextran sulfate sodium colitis. This was a result of impaired shedding of EGF-R ligands resulting in failure to phosphorylate STAT3 via the EGF-R and, consequently, in defective regeneration of epithelial cells and breakdown of the intestinal barrier. Besides regulating the systemic availability of the proinflammatory cytokine TNF, our results demonstrate that ADAM17 is needed for vital regenerative activities during the immune response. Thus, our mouse model will help investigate ADAM17 as a potential drug target.